Time-restricted feeding improves metabolic and endocrine profiles in mice with polycystic ovary syndrome - Han, Yan; Lin, Baiwei; Lu, Wenjing; Wang, Xu; Tang, Wenshuai; Tao, Xinge; Cai, Han; He, Chunmei; Liu, Changqin (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathy disorders in premenopausal women, which is characterized by hyperandrogenemia, anovulation, and polycystic ovarian morphology (PCOM). Time-restricted feeding (TRF) is a new intermittent restriction dietary pattern, which has been shown to have positive benefits on obesity and glycolipid metabolism disorders. We aimed to explore the effect of the feeding regimen (ad libitum vs. TRF) on the glycolipid metabolism and reproductive endocrine disorders in a PCOS mouse model induced by continuous subcutaneous administration of dihydrotestosterone (DHEA) for 21 days. Mice were fed a high-fat diet (HFD) for 8 weeks on an ad libitum or time-restricted diet (from 10:30 pm to 6:30 am). Compared to control mice, PCOS mice that received TRF treatment had significantly lower body weight, reduced adiposity, lower area under the curve of glucose response (AUC) in the oral glucose tolerance test (OGTT), and lower AUC in the insulin tolerance test (ITT). TRF also ameliorated lipid metabolism, as shown by a reduction in plasma lipid profiles (triglycerides and cholesterol) and triglyceride content in the liver of PCOS mice. In terms of reproduction, plasma androgen level, plasma estrogen (E2) level, and luteinizing hormone (LH) / follicle stimulating hormone (FSH) ratio in PCOS mice were significantly reduced after 8 weeks of TRF treatment. In addition, ovarian histology showed that TRF inhibits cyst formation and promotes corpus luteum formation. In conclusion, TRF improved metabolic and endocrine profiles in mice with PCOS.